Mastery approach and performance approach: the differential prediction of organizational citizenship behavior and workplace deviance, beyond HEXACO personality - Louw, K.; Dunlop, P.; Yeo, G.; Griffin, Mark (Springer Netherlands, 2016)
© 2016, Springer Science+Business Media New York. Goal orientation has become one of the most studied motivational constructs in the psychology literature. However, in organizational contexts, the research focus to date has largely centered on the relationship between goal orientation and task performance—neglecting the valuable contribution of non-task work behaviors, such as workplace deviance and organizational citizenship behavior (OCB) to organization functioning. In this paper, we addressed this gap in the literature by investigating the differential prediction of performance approach and mastery approach goal orientation on workplace deviance and OCB, beyond personality correlates. We hypothesize that performance approach orientation is positively associated with workplace deviance and mastery approach orientation is positively associated with OCB. A sample of employed participants (n = 114) provided self-reports of goal orientation, workplace deviance, OCB and personality. Additionally, participants nominated a well-acquainted peer to provide peer-reports of their personalities. When controlling for personality, performance approach orientation positively predicted workplace deviance whereas mastery approach orientation positively predicted organizational citizenship behavior. This study is the first to our knowledge to explore the relationships between goal orientation and non-task work behaviors and to show that goal orientation adds to the understanding of workplace deviance and OCB, beyond personality. Practical implications and directions for future research are discussed.